Uma nova espécie de Diaptomidae (Crustacea, Copepoda) "Diaptomus" negrensis das águas pretas perto de Manaus - Andrade, Elsa Rodrigues de; Brandorff, Gerd-oltmann (Acta Amazonica, 1975)
A description of a new species of Diaptomidae "Diaptomus" negrensis is given with a diagnosis. The variation of this species is very little. It has been found in various lakes at the left margin of the Rio Negro (Amazonas) near the city of Manaus. A map shows the distribution. A possible relationship with "Diaptomus" alter Herbst, 1960 is discussed but a certain relationship can\'t be given.